THE EFFECT OF RELIABILITY OF FUNCTIONAL SYSTEMS ON THE EFFICIENCY OF THE TECHNICAL OPERATION OF THE AIRCRAFT - E. D. Gerasimova; N. N. Smirnov; O. Nambat (Научный вестник МГТУ ГА, 2017)
The article deals with the estimation algorithm for functional system reliability influence on the aircraft technical maintenance. The research results which allow to estimate the functional system reliability influence on the aircraft technical maintenance process are provided. The aircraft maintenance process effectiveness implies the maintenance procedures including pre-flight preparation, the flight itself, technical maintenance and storage.The research was aimed at forecasting the aircraft technical maintenance process considering the functional system reliability, with special attention payed to failure-free operation. The term failure-free operation stands for the ability to execute a required function within a given time interval at given conditions.The objects of maintenance -aircraft functional systems and their components have a great degree of failure-free operation, which has been a design requirement and is supported at aircraft maintenance and operation. Failures and malfunctions are seldom events. This fact leads to a limited statistic maintenance surveillance database. Classical methods of statistical analyses do not provide the sufficient fiducial probability for functional system failure-free operation estimation. Thus these methods do not allow to estimate its influence on the aircraft technical maintenance process effectiveness.In order to solve this problem it is suggested to use the method of flow diagrams and random sample statistical method for failure-free operation estimation-statistical modeling (Monte-Carlo Method). Reliability flow diagram method allowed to determine the functional system failure-free operation random sample dependence on the technical maintenance frequency.The initial data were: the functional system flow diagram, the list of the main equipment, functional system equipment failure random sample data. The use of statistical modeling allowed to estimate the dependence of functional system reliability (failure-free operation) on the technical maintenance frequency for expanded statistical database (a number of functional system maintenance and operation procedures).